1991
DOI: 10.1111/j.1365-2125.1991.tb03889.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the anti‐inflammatory drug ximoprofen in healthy young and elderly subjects: comparison with elderly rheumatic patients.

Abstract: The pharmacokinetics of ximoprofen were studied in young and elderly subjects after single and repeated doses up to 30 mg. In healthy elderly subjects (30 mg dose), a mean peak plasma drug concentration of 1.78 micrograms ml‐1 +/‐ 0.83 s.d. occurred at a mean time of 1.95 h +/‐ 1.40 s.d. and, thereafter, concentrations declined monoexponentially with a mean half‐life of 3.8 h +/‐ 1.4 s.d. Comparison of these data with those from younger healthy subjects showed that peak drug concentrations, areas under the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…All alterations in pharmacokinetics have been suggested to be related to decreased protein binding and subsequent changes in the volume of distribution and in some cases changes in metabolism of the medication .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All alterations in pharmacokinetics have been suggested to be related to decreased protein binding and subsequent changes in the volume of distribution and in some cases changes in metabolism of the medication .…”
Section: Methodsmentioning
confidence: 99%
“…Studies of other acetic acid derivatives, etodolac, bromfenac and indomethacin, in CKD and ESRD patients, do not suggest that any dose adjustment is necessary (167)(168)(169). Propionic acid derivatives (the -profens): 11 studies identified CKD Studies evaluating ketoprofen, ximoprofen and benoxaprofen have shown increased half-life in CKD (170)(171)(172)(173).…”
Section: Dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…These data are presented as sigmoidal Emax model parameter estimates. The data from one subject (13) were not included since they were not amenable to modelling. No …”
Section: Pharmacodynamics Of (S)-ketoprofenmentioning
confidence: 99%
“…A low percentage of the dose of such drugs is cleared renally in unchanged form yet, paradoxically, a number of them have diminished clearance in patients with renal dysfunction, or in elderly patients in whom renal function is reduced [8][9][10][11][12][13][14]. Moreover, coadministration of probenecid has caused a decrease in the plasma clearance of these NSAIDs [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%